2019
DOI: 10.1016/j.cub.2019.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Cambrian Sessile, Suspension Feeding Stem-Group Ctenophores and Evolution of the Comb Jelly Body Plan

Abstract: Highlights d We describe a new early Cambrian fossil with a polypoid body plan from Chengjiang d It is related to the supposed cnidarian Xianguangia and the iconic Dinomischus d The fossils possess very large ciliary structures otherwise seen only in ctenophores d We show that these fossils form a grade of stem-group ctenophores

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
120
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(133 citation statements)
references
References 62 publications
12
120
1
Order By: Relevance
“…Xianguangia sinica is a tentaculate polyp known from the Chengjiang BST and generally interpreted as a stem group cnidarian (Ou et al, 2017). However, Xianguangia was recently reinterpreted as a benthic stem group Ctenophore (Zhao et al, 2019), though this interpretation may prove controversial because of the presence of mesenteries (Daley & Antcliffe, 2019). Analysis of the taphonomy of these Lagerstätte has shown that anoxic and reducing conditions are common and regularly cited as amongst the primary causative agents in the preservation of the soft-bodied animals (Allison, 1988a;1988b;Anderson, Tosca, Gaines, Mongiardino Koch, & Briggs, 2018;Butterfield, 1990;Gaines et al, 2008Gaines et al, , 2012Gaines et al, , 2005.…”
Section: F I G U R Ementioning
confidence: 99%
“…Xianguangia sinica is a tentaculate polyp known from the Chengjiang BST and generally interpreted as a stem group cnidarian (Ou et al, 2017). However, Xianguangia was recently reinterpreted as a benthic stem group Ctenophore (Zhao et al, 2019), though this interpretation may prove controversial because of the presence of mesenteries (Daley & Antcliffe, 2019). Analysis of the taphonomy of these Lagerstätte has shown that anoxic and reducing conditions are common and regularly cited as amongst the primary causative agents in the preservation of the soft-bodied animals (Allison, 1988a;1988b;Anderson, Tosca, Gaines, Mongiardino Koch, & Briggs, 2018;Butterfield, 1990;Gaines et al, 2008Gaines et al, , 2012Gaines et al, , 2005.…”
Section: F I G U R Ementioning
confidence: 99%
“…The most famous of these are the 'bizarre crab' Anomalocaris and the 'mind-bending' Hallucigenia. The fossils described by Zhao and colleagues [8] are just as enigmatic, marking this work as an important contribution to the field owing to the detailed descriptions and images of a new taxon, Daihua sanqiong, and of enlightening new specimens of previously described taxa, including Xianguangia, Dinomischus and Siphusauctum. This last taxon has colloquially been called the 'tulip animal', which is a fairly accurate visual description of its overall anatomy [9].…”
mentioning
confidence: 91%
“…These provide another tangible record of evolution and are particularly abundant and well preserved during the first major burst of animal evolution, the Cambrian explosion. A new study in this issue of Current Biology by Yang Zhao, Jakob Vinther and colleagues [8] describes bizarre Cambrian fossils and places them in the ctenophore stem lineage, forming a close alliance between ctenophores and cnidarians ( Figure 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations